1995
DOI: 10.1021/ja00140a009
|View full text |Cite
|
Sign up to set email alerts
|

More on Adamantene

Abstract: At high dilution and temperature adamantene undergoes a retro Diels-Alder cycloaddition to a triene, as well as retro-insertion reactions to give carbenes. 1,2-Diiodoadamantane and 3-diiodomethylnoradamantane react with methyllithium in the gas phase to give adamantene, which is efficiently reduced to adamantane under these conditions. Addition of adamantene to butadiene occurs in 4 + 2 and 2 + 2 fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Other examples of prepared anti‐Bredt compounds include bicyclo[2.2.2]oct‐1‐ene ( G ) (Figure ), 8‐methylenebicyclo[3.2.1]octa‐1,6‐diene ( H ) (Figure ), and bicyclo[3.2.2]nona‐1,6,8‐triene ( I ) (Figure ); all of these compounds are highly reactive. Adamantene ( J ) (Figure ) and substituted analogues have been prepared. DFT computations of adamantene by Shustov and Liu indicate that the singlet is lower than the triplet state by 11.4 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of prepared anti‐Bredt compounds include bicyclo[2.2.2]oct‐1‐ene ( G ) (Figure ), 8‐methylenebicyclo[3.2.1]octa‐1,6‐diene ( H ) (Figure ), and bicyclo[3.2.2]nona‐1,6,8‐triene ( I ) (Figure ); all of these compounds are highly reactive. Adamantene ( J ) (Figure ) and substituted analogues have been prepared. DFT computations of adamantene by Shustov and Liu indicate that the singlet is lower than the triplet state by 11.4 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The Jones , and Michl ,, groups were the among first to study and use bridgehead carbenes as a route to bridgehead alkenes . Among the compounds they studied were adamantene ( 3a ) ,, and homoadamantene ( 3b ). , The Platz group generated 3a and 3b photochemically from noradamantyldiazirine ( 1a ) and adamantyldiazirine ( 1b ), respectively (Scheme ). , The photochemistry of both noradamantyldiazirine ( 1a ) and adamantyldiazirine ( 1b ) is quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…The Jones , and Michl ,, groups were the among first to study and use bridgehead carbenes as a route to bridgehead alkenes . Among the compounds they studied were adamantene ( 3a ) ,, and homoadamantene ( 3b ). , The Platz group generated 3a and 3b photochemically from noradamantyldiazirine ( 1a ) and adamantyldiazirine ( 1b ), respectively (Scheme ). , The photochemistry of both noradamantyldiazirine ( 1a ) and adamantyldiazirine ( 1b ) is quite complex. In 2001, Platz and co-workers reported that the photolysis of noradamantyldiazirine ( 1a ) leads to adamantene ( 3a ) through the excited state of the diazirine, bypassing noradamantylcarbene ( 2a ). , They computed the singlet 2a ⇌ 3a equilibrium to greatly favor 3a by 32.4 kcal/mol (B3LYP/6-31G*) and a nominal 0.35 kcal/mol barrier for the conversion of singlet adamantylcarbene to adamantene …”
Section: Introductionmentioning
confidence: 99%
“…Both species can be generated photochemically from 3‐noradamantyldiazirine ( 6 ) and are in a photochemical equilibrium with carbene 7 under matrix isolation conditions (Scheme ) 15b. In solution, they are fleeting and dimerize in benzene or hexane, or react with the solvent in methanol or acetic acid 15a,c. 16 Aside from the prospect to stabilize these species by encapsulation, dynamic octamine hemicarcerands 1 a – c possess another unique property that makes them useful as nanoreactor, namely the ability to alter their dynamics and stability through addition of acid and/or water, which will influence their molecular recognition properties and guest exchange kinetics 12d,q.…”
Section: Introductionmentioning
confidence: 99%